Massage in children with cancer: effectiveness of a protocol - Luís Manuel da Cunha Batalha; Aida A.S.C. Mota (Elsevier, 2013)
Objectives: massage can help relieve pain, although empirical evidence is scarce and contradictory. This study aims to assess the effectiveness of a massage protocol in relieving pain in children hospitalized with cancer. Methods: a randomized, controlled, and single-blind trial was performed in a sample of 52 children aged between 10 and 18 years who were hospitalized in a pediatric cancer ward. The intervention consisted of the implementation of a massage protocol with three sessions of 20 to 30 minutes on alternate days over a one-week period. The effectiveness of the protocol was evaluated by assessing pain using the Brief Pain Inventory (BPI), while the effectiveness of each massage session was measured using the Visual Analogue Scale (VAS). Results: the massage protocol was only effective in reducing the interference of pain in walking (p < 0.05), although it also contributed to relieve pain and its impact on the children's activities. After each massage session, the intensity of the pain experienced by the child decreased (p < 0.001). Conclusions: despite the small sample size, massage therapy appears to be a useful intervention in reducing pain in children with cancer. However, there are still questions regarding the effectiveness of this massage protocol. The authors recommend its use due to its contribution to the promotion of the child's well-being and quality of life. Resumo: Objetivos: a massagem é uma intervenção que pode contribuir para o alívio da dor, embora as evidências empíricas sejam escassas e contraditórias. O objetivo deste trabalho foi avaliar a eficácia de um protocolo de massagem no alívio da dor na criança internada, com patologia oncológica. Métodos: através de um estudo randomizado e controlado com cegamento simples, foram estudadas 52 crianças, com idades compreendidas entre os 10 e os 18 anos, internadas num serviço de oncologia pediátrica. A intervenção consistiu na aplicação de um protocolo de massagem de três sessões com duração entre 20 a 30 minutos em dias alternados durante uma semana. A eficácia do protocolo foi medida através da avaliação da dor com a aplicação do Inventário Resumido de Dor e a eficácia de cada sessão de massagem pela Escala Visual Analógica (EVA). Resultados: o protocolo de massagem apenas se revelou eficaz na diminuição da interferência da dor no andar (p < 0,05), apesar de ter contribuído para o alívio da dor e sua interferência nas atividades da criança. Após cada sessão de massagem a intensidade da dor sentida pela criança diminuiu (p < 0,001). Conclusões: apesar da reduzida dimensão da amostra, a massagem parece ser uma intervenção útil no alívio da dor da criança que sofre de patologia oncológica, embora permaneçam dúvidas quanto à eficácia deste protocolo de massagem. Todavia, os autores recomendam a sua utilização pela sua contribuição na promoção do bem-estar e qualidade de vida da criança. Keywords: Pain, Massage, Child, Cancer, Palavras-chave: Dor, Massagem, Criança, Câncer